Analisis Pengaruh Penambahan Suplai Daya 1000 MW Terhadap Performansi Jaringan Backbone 500 kV - Mudjiono; Imron Ridzki; Priya Surya Harijanto (Politeknik Negeri Malang, 2021)
Based on the Decree of the Minister of Energy and Mineral Resources (ESDM) Number 0074.K / 21 / MEM / 2015 concerning the Ratification of the 2016-2025 Electricity Supply Business Plan (RUPTL), the load growth every year has increased. Therefore, there will be additional Generating Units with a capacity of 1000 MW at PLTU Paiton, it is necessary to analyze the effect of additional loads in 2017 - 2022 on the 500 KV GITET system before and after the addition of a 1000 MW generator. Based on the analysis, it is known that the additional power of 1000 MW will strengthen the Paiton GITET reserve margin in bearing the load growth, it can be seen from the reserve margin value before the addition of power plants by 16% and after the addition of 29%. For the ability of the Paiton - Grati GITET transmission line until 2022, the load is 62% with a power loss of 35.41 MW (2.85%) and the load on the Paiton - Kediri GITET transmission line is 62% with a power loss of 35.41 MW (2.85%) indicates that the channel still in good shape. In addition, the load condition for the IBT transformer until 2022 is 84%, it can be concluded that the transformer is in good condition